2017
DOI: 10.7554/elife.27669
|View full text |Cite
|
Sign up to set email alerts
|

Directing visceral white adipocyte precursors to a thermogenic adipocyte fate improves insulin sensitivity in obese mice

Abstract: Visceral adiposity confers significant risk for developing metabolic disease in obesity whereas preferential expansion of subcutaneous white adipose tissue (WAT) appears protective. Unlike subcutaneous WAT, visceral WAT is resistant to adopting a protective thermogenic phenotype characterized by the accumulation of Ucp1+ beige/BRITE adipocytes (termed ‘browning’). In this study, we investigated the physiological consequences of browning murine visceral WAT by selective genetic ablation of Zfp423, a transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 55 publications
0
37
0
Order By: Relevance
“…An increasing number of studies support that activation of the thermogenic program in the adipose tissue beneficially impacts on glucose and lipid homeostasis and insulin sensitivity, especially in the context of energy overload and obesity [9,10,22,23]. In the HFD-fed foz/foz mouse model we used, low-thermogenic BAT function accompanies severe insulin resistance and morbid obesity [11].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies support that activation of the thermogenic program in the adipose tissue beneficially impacts on glucose and lipid homeostasis and insulin sensitivity, especially in the context of energy overload and obesity [9,10,22,23]. In the HFD-fed foz/foz mouse model we used, low-thermogenic BAT function accompanies severe insulin resistance and morbid obesity [11].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the protective role of SAT, excess VAT is indeed associated with a cluster of metabolic abnormalities referred to as metabolic syndrome. Research about VAT has been getting more and more attention . According to the first reports of Oberkofler et al, reduced UCP1 mRNA levels in VAT of humans with obesity had been observed .…”
Section: Discussionmentioning
confidence: 99%
“…Our own work on the transcription factor ZFP423 also sheds insight into plasticity of mature adipocytes (22,33). Zfp423 expression is enriched in white versus brown adipocytes and is suppressed in fat cells upon cold exposure or direct activation of b3-adrenergic signaling (22).…”
Section: Beige Cells Can Arise From Differentiated Unilocular Adipocytesmentioning
confidence: 99%